The examination of pecan price differences using spatial correlation estimation - Sarmiento, Camilo; Wojciech J., Florkowski (Taylor and Francis Group, 2005)
A spatial analysis is used to model factors that explain the price received by pecan growers. Besides the statistical aspect of the study focussing on spatial utoregressive residuals, the economic analysis of the paper identifies linkages between the price for in-shell pecans received by growers and the characteristics of the orchard, production costs and resources, and the orchard location.

Se utiliza un análisis espacial para modelar factores que explican el precio recibido por productores de nueces pecanas. Además del aspecto estadístico del estudio centrado en residuos autorregresivos espaciales, el análisis económico del artículo identifica vínculos entre el precio de las nueces pecanas con cáscara recibido por los productores y las características del huerto, costos y recursos de producción, y la ubicación del huerto.
Keywords: Costos de producción; Econometría; Nueces pecanas - Investigaciones - Análisis de costos; Nueces pecanas - Producción - Aspectos económicos; Productos agrícolas - Aspectos económicos; Production costs; Econometrics; Pecans - Research - Cost Analysis; Pecans - Production - Economic aspects; Agricultural products - Economic aspects